Chapter The building materials of "Rocca Vecchia" (Old Fortress) in the Gorgona Island - De Vita, Francesca (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The research examines the building materials of the ancient fortress known as Rocca Vecchia, in the Gorgona Island, built by the Republic of Pisa and commonly dated to the 13th century. Particular attention is paid to the composition of the artificial stone materials (bricks, bedding mortars, plasters and renders) in order to better understand and define the different construction phases. The results will be useful from the historical point of view and for the future conservation intervention which will have to involve a group of prisoners who will also have the task of the subsequent maintenance.